COLREG regel 17 - En analys av befälens bedömningar - Elfwering, Henning; Thorsander, Carl Hannes (My University, 2017)
The officer of the watch (OOW) is the one who make the final decisions regarding the ship's manoeuvring. The International Regulations for Preventing Collisions at Sea (COLREG), is the regulation that guides the OOW’s decision. Since the regulations need to cover all situations at sea, it has a general formulation. The result is that the OOW gets guidelines for what he must do, while the decision on when that action must be carried out is left out to the OOW for each specific situation. This study examines how the factors: rank, age, years at sea, ship type and size influence on what decision the OOW's will take related to COLREG Rule 17. Using a questionnaire distributed by the Marine Officers' Association to its members, data was collected and analyzed. The results are discussed in relation to previous research in the area. The final result show that the factors mentioned above have only small impact on the OOW's decision. Of these factors, the ship’s type holds the highest impact in relation to the other factors.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport